1983
DOI: 10.2134/jeq1983.00472425001200010012x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ozone and Sulfur Dioxide on Tuber Yield and Quality of Potatoes

Abstract: Air pollution injury of the potato plant (Solanum tuberosum L.) has been documented previously, but potato yield losses have not been estimated in replicated experiments having controlled exposures to ozone (O3) and sulfur dioxide (SO2) A controlled‐environment study involving the speckle‐leaf‐sensitive cultivar ‘Centennial Russet’ was conducted to examine the effects of chronic exposure to O3 and SO2 on plant growth and tuber yield and quality.Ozone, at the highest seasonal dose (44.2 ppm‐h), reduced leaf dry… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

1983
1983
2017
2017

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(11 citation statements)
references
References 0 publications
0
11
0
Order By: Relevance
“…These changes reduced the total weight of tubers produced under elevated O 3 in the absence of effects on overall tuber number. Ozone‐induced reductions in total tuber number have also been observed in experiments using container‐grown plants (Foster et al. , 1983b; Pell & Pearson, 1984), although Foster et al .…”
Section: Discussionmentioning
confidence: 79%
See 3 more Smart Citations
“…These changes reduced the total weight of tubers produced under elevated O 3 in the absence of effects on overall tuber number. Ozone‐induced reductions in total tuber number have also been observed in experiments using container‐grown plants (Foster et al. , 1983b; Pell & Pearson, 1984), although Foster et al .…”
Section: Discussionmentioning
confidence: 79%
“…In tests of the O 3 sensitivity of 12 potato cultivars in the United States, Heggestad (1973) concluded that the more sensitive varieties originated from areas experiencing low ambient O 3 concentrations. In OTC experiments in California, Foster et al . (1983b) showed that a cumulative dose of 44.2 µmol mol −1 h O 3 induced severe foliar damage and reduced tuber yield by 45%; however, other studies of defoliation by Colorado beetle indicate that potato is capable of compensating for extensive foliar damage (Hare & Moore, 1988) as no yield losses occurred even after 50% defoliation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Severely injured leaves became chlorotic, followed by progressive necrosis, defoliation and accelerated plant death (Foster et al, 1983). However, estimates of visual injury did not correlate with yield reduction for wheat (Decoteau et al, 1986) and spinach (Heagle et al, 1979).…”
Section: Discussionmentioning
confidence: 94%